KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KECAMATAN CIMALAKA KABUPATEN SUMEDANG - Bunga Tri Wahyuni; Rika Kusdinar; Lalas Sulastri (LPPM UNSAP, 2026)
This study aims to measure the extent of the Quality of Population Administration Services in Cimalaka District, Sumedang Regency. The performance measurement of this organization is assessed through Tangible Evidence, Reliability, Responsiveness, Assurance, and Empathy. The research method used in this study is a qualitative research method, conducted in a natural setting, with an emphasis on meaning rather than generalization. The informants were selected using purposive sampling, consisting of: the Sub-District Secretary, the Head of Public Services Section, Community Member I, and Community Member II. Data collection techniques used include literature review and field studies, consisting of observation, interviews, documentation, and triangulation. Meanwhile, the data processing procedures in this study involve data reduction, data display, and conclusion drawing/verification. Based on the results of the study, it can be concluded that the quality of population administration services in Cimalaka District, Sumedang Regency has been running well. However, in its implementation, several obstacles were still found, such as the limited number of staff, suboptimal service facilities, and the underutilization of information technology. To overcome these obstacles, various efforts have been made, such as improving human resource capacity through training, enhancing facilities and infrastructure, and developing technology-based service systems. This study is expected to serve as an evaluation material and input for the Cimalaka District Office in continuously improving the quality of population administration services.